2019
DOI: 10.1016/j.pbj.0000000000000028
|View full text |Cite
|
Sign up to set email alerts
|

The role of flavonoid antioxidant, morin in improving procarbazine-induced oxidative stress on testicular function in rat

Abstract: Background:Procarbazine (PCZ) is an effective chemotherapeutic drug used in the treatment of lymphoma; however, oxidative stress–mediated testicular toxicity is a major side effect. Recently, therapeutic intervention using flavonoids against oxidative stress–related pathologies is gaining more attention. Morin (MOR) is a natural flavonoid with proven antioxidant activity. This study was designed therefore to evaluate the potential role of MOR in ameliorating PCZ-induced testicular oxidative stress and altered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 52 publications
3
14
0
Order By: Relevance
“…The increase in abnormal sperm coupled with decrease in motility, viability and total sperm cell count is consistent with an earlier report on BCT (Adeniyi et al, 2009;Abdulrahman and Mustafa, 2019). A significant improvement was observed when MOR was administered along with BCT which is in agreement with previous reports on the protective effects of MOR on testicular function (Olayinka et al, 2019).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The increase in abnormal sperm coupled with decrease in motility, viability and total sperm cell count is consistent with an earlier report on BCT (Adeniyi et al, 2009;Abdulrahman and Mustafa, 2019). A significant improvement was observed when MOR was administered along with BCT which is in agreement with previous reports on the protective effects of MOR on testicular function (Olayinka et al, 2019).…”
Section: Discussionsupporting
confidence: 92%
“…represents the dosage for the treatment of a locally advanced prostate cancer, 100 mg/kg/d MOR p.o. was selected on the basis of its effectiveness in earlier studies (Kolvenbag and Nash, 1999;Kuzu et al, 2019;Olayinka et al, 2019).…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…This increases fertility and decreases the percentage of abnormal spermatozoa. It produces a positive feedback loop that also leads to increased testosterone levels (Olayinka et al, 2019). The normal shape of the spermatozoa will directly affect the spermatozoa motility and integrity (Jakubik-Uljasz et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Testicular toxicity is also an adverse effect of some other anticancer agents, e.g., procarbazine. Olaynka et al [28] found that morin significantly restored the procarbazine-induced abnormal sperm parameters (count, motility, percentage of normal sperm). Some studies claim that morin protects testicular tissue from morphological injuries and pathology of sperm count and viability induced by titanium dioxide nanoparticles [27,29].…”
Section: Discussionmentioning
confidence: 99%